The impact of risk factors on ECG parameters and quality of life in post-myocardial infarct patients - Alen Džubur; Azra Nalbantić; Amela Džubur; Esad Pepić; Mevludin Mekić; Jasmin Mušanović; Pešto Senad (Archives of Global Professionals, 2017)
Introduction: Many epidemiological studies have shown that there are numerous risk factors for acute coronary disease. The aim is to determine the effect of risk factors on the echocardiographic changes and quality of life in patients treated with different methods 1 year after myocardial infarction. Methods: The research was a prospective-retrospective, clinical, epidemiological study and was conducted at the Clinic of Cardiology, University Clinical Center Sarajevo. Patients were divided into four groups based on the therapy treatment they got. The patients were divided into four groups based on the therapy treatment they received. The first group consisted of 40 patients who had had myocardial infarction and were treated with medications. The patients in the groups II and III were treated with percutaneous coronary intervention (PCI) [who immediately after incident underwent primary PCI or delayed PCI], and each group consisted of 40 patients. The group IV consisted of 40 patients, who underwent surgical revascularization (coronary artery bypass surgery). After the treatments have finished, an echocardiogram was performed on every patient. The Short Form (SF)-36 health survey was used for testing the life quality. Echocardiogram and the quality of life (QoL) testing were repeated a year after the treatment. Results: The study included 160 patients with a history of myocardial infarction, of which 130 (81.3%) were men, and 30 (18.8%) were women. The average age in the total sample was 54.9 ± 8.8 years. The review of risk factors' presence showed that in the total sample, most present was hypertension with 134 (83.8%), smoking with 120 (75.0%), and hypercholesterolemia with 110 or 68.8% of patients. Hypertension showed a statistically significant negative effect on the SF-scales only in the group III according to the mental health (P = 0.020), social functioning (P = 0.013), and pain (P = 0.011). A statistically significant effect of smoking was observed in the group III according to left ventricular internal dimension in end-diastole (P = 0.000) and left ventricular internal dimension in end-systole (P = 0.001) in the sense that smokers have the higher values of these parameters, and negative to ejection fraction (EF) (P = 0.001) in the sense that smokers have lower EF. In the group IV, positive correlation was observed to EF (P = 0.038), and negative toward the mitral regurgitation (P = 0.032). Conclusion: High blood pressure negatively affected the QoL. Smoking is negatively associated with all observed echocardiographic parameters in all the groups except with the size of the left atrium.